2015
DOI: 10.12681/ppej.178
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Profiles of Poor Readers/Good Spellers and Good Readers/Poor Spellers in a Consistent Orthography: A Retrospective Analysis

Abstract: Abstract. Reading and spelling are closely related to each other, but empirical evidence shows that they can also dissociate. The purpose of this study was to examine the cognitive profiles of good readers/poor spellers and poor readers/good spellers in a relatively consistent orthography (Greek). One hundred forty children were administered measures of phonological awareness, rapid automatized naming, phonological short-term memory, and orthographic knowledge in grades 1 and 2. Their performance in reading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
4
1
Order By: Relevance
“…As expected, Manolitsis and Georgiou [46] found more SD (8.1%) than RD (5.1%) in their sample of native Greek-speaking children. However, the estimated prevalence rates of SD and RD were comparable in Moll and Landerl's [47] [41,46]. Although a larger discrepancy is observed between forward and backward regularity in German, a smaller difference has found between the estimated prevalence rates of SD and RD in German-speaking samples.…”
Section: Dissociation Between Reading and Spelling Difficulties In Chsupporting
confidence: 77%
See 2 more Smart Citations
“…As expected, Manolitsis and Georgiou [46] found more SD (8.1%) than RD (5.1%) in their sample of native Greek-speaking children. However, the estimated prevalence rates of SD and RD were comparable in Moll and Landerl's [47] [41,46]. Although a larger discrepancy is observed between forward and backward regularity in German, a smaller difference has found between the estimated prevalence rates of SD and RD in German-speaking samples.…”
Section: Dissociation Between Reading and Spelling Difficulties In Chsupporting
confidence: 77%
“…Although a larger discrepancy is observed between forward and backward regularity in German, a smaller difference has found between the estimated prevalence rates of SD and RD in German-speaking samples. Such observation does not fully support the hypothesis of Manolitsis and Georgiou [46] that difference in forward and backward regularity has a direct relationship with the resulting prevalence of dissociated difficulties. While the effect of orthographic depth on reading and spelling dissociation is inconclusive, it is evident that much lesser is known about orthographically opaque languages.…”
Section: Dissociation Between Reading and Spelling Difficulties In Chcontrasting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, children can probably read accurately a word (e.g., bread), even if they do not have access to a precise orthographic representation (e.g., bred). 5 Evidence in support of this argument can be drawn also from studies examining the double dissociation between reading and spelling (e.g., Frith, 1980;Manolitsis & Georgiou, 2015;Moll & Landerl, 2009). Frith (1980) was the first to report a group of children who were adequate readers but "atrocious" spellers.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding is that the reading fluency problems experienced by children with dyslexia in transparent orthographies are related to visual-verbal processing deficits, as measured by rapid naming tasks requiring children to name aloud a series of elements as for example objects, colours, letters or digits as accurately and quickly as possible. In contrast, visual-verbal processing deficits are not usually observed in children with SpD ( Bar-Kochva & Amiel, 2016;Gangl, Moll, Jones, et al, 2018;Manolitsis & Georgiou, 2015;Moll & Landerl, 2009;Torppa et al, 2017;Wimmer & Mayringer, 2002). Evidence on phonological processing deficits (indicating problems in the manipulation of phonemes) is less straightforward, as some studies reported them not only for dyslexia, but also for SpD (Bar-Kochva & Amiel, 2016;Fayol et al, 2009;Torppa et al, 2017;Wimmer & Mayringer, 2002), while others found only mild or no phonological impairments Manolitsis & Georgiou, 2015;Moll & Landerl, 2009).…”
Section: Introductionmentioning
confidence: 98%